Work Environment, Rewards, Punishment, and Employee Performance - Putu Adi Sutha Prasetya Pucangan; Anak Agung Media Martadiani; Ni Nyoman Suriani (International Journal of Islamic Business and Management Review, 2026)
This study analyzes the influence of work environment, rewards, and punishments on employee performance at PT Bina San Prima Denpasar Branch. A quantitative approach was used involving 52 respondents who were determined through the Slovin formula. Data were analyzed using multiple linear regression with the help of SPSS. The results of the study show that the work environment, rewards, and punishments simultaneously have a positive and significant effect on employee performance. Partially, the variables of work environment and reward have a positive and significant effect, while punishment has a negative and insignificant effect. These findings underscore the importance of creating a supportive work environment and implementing an effective reward system to improve employee performance, while existing punishment mechanisms have not made a real contribution to improving performance. This research provides empirical evidence for organizations to prioritize motivational and environmental factors in an effort to strengthen employee productivity